An Extended Study Regarding the Phenomenon of Optical Flicker and the Design Details of the Statistical Scale Designed by the Department of Electrical Engineering at the Higher Institute of Engineering Technology/Tripoli - Shffat, Salem; Almusraty, Nadya; Bettamer, Majdi (Conference On Engineering Science and Technology, 2021)
The phenomenon of light tremors causes severe anxiety, tension and headaches, and in some cases it may lead to epilepsy for those who are sensitive to this type of nerve stimulation, and it occurs due to continuous or almost continuous fluctuations in the intensity of lighting. It does not mean here single changes regardless of their intensity, but rather that change that has a pattern and nature of continuous stress in time and its effect is of a cumulative statistical nature. This stress is at its highest intensity when the frequency of these changes is 8.8 Hz. It is known that the electrical power of the incandescent lamp is proportional to the root mean square of the instantaneous value RMS of the voltage wave. Therefore, these voltage disturbances must be monitored, which appear as the delay of the voltage wave amplitudes. This type of disturbance occurs due to the operation of the voltage regulators of the synchronous generators or due to the constant change in the value of the loads on the network, especially non-linear ones. Due to the importance of this topic to human safety, the European type EN-60150 has set permissible values ​​for the value of the coefficient of Pst which gives the probability of occurrence of tension due to light jitter, based on the measurement of the instantaneous value of the voltage wave for ten minutes, corresponding to the Plt coefficient which is calculated based on the first parameter as a geometric mean for two hours, European style EN-50160 sets the limits for weekday continuous measurement. The meter is a device that consists of several functional boxes that end with a statistical analysis. Accordingly, the International Electrotechnical Council has issued a standard pattern IEC61000-4-15 that describes the box diagram for a measure of the effect of the phenomenon of light disturbance on human behavior. In this research paper, design details not mentioned in the patterns were given, as well as a computer program on Matlab for a digital scale based on a design for the Higher Institute of Engineering Technologies/Tripoli